PENGARUH DISKON HARGA TERHADAP PURCHASES INTENTIONS YANG DIMEDIASI OLEH KEPERCAYAAN KONSUMEN DALAM PEMBELIAN SEPATU OLAH RAGA SECARA ONLINE DI KOTA BANDA ACEH - Muhammad Deza; Permana Honneyta Lubis (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2022)
This study aims to determine the effect of price discounts on the intention to buy sports shoes online that are mediated by trust. This research was conducted in Banda Aceh City. The study population was all teenage consumers aged 18-21 who were domiciled in the city of Banda Aceh and had purchased sports shoes online. whose numbers cannot be known with certainty. The sample size is set at 150 teenagers. Data collection is done by distributing question sheets (questionnaires). Primary data were analyzed by path analysis with the help of SPSS devices.The results of the study explain that price discounts have a significant effect on increasing adolescent consumer confidence in purchasing sports shoes online in Banda Aceh City. Adolescent trust has a significant effect on the intention to buy sports shoes online in Banda Aceh City. Discounted prices have no significant effect on the purchase intention of sports shoes in Banda Aceh City. Consumer trust can enhance the role of mediating the effect of price discounts on the intention to buy sports shoes online.